Impact of Wari-Maro classified forest management plan implementation on the structure and specific diversity of vegetation types in Benin (West Africa) - MENSAH, K.S. Gildas; AROUNA, OUSSENI; TOKO IMOROU, ISMAÏLA; THOMAS, OMER B.; ZAKARI, Soufouyane (My University, 2018)
The participatory management plan is a technical, legal and social device that joins the objectives of biodiversity conservation and the socio-economic needs of local populations. This research work aims to evaluate the impact of Wari-Maro classified forest management plan implementation on the structure and specific diversity of vegetation types. The methodological approach followed is based on the comparison of the dendrometric parameters and plant diversity parameters before and after the management plan implementation. The phytosociological and dendrometric database before the management plan was compiled with data from the forest inventory conducted by PAMF project in 2004 and others work. The forest and phytosociological inventories were carried out on the plots (70) from the forest inventory of PAMF project (2004) following the same methodological principles. The Shannon diversity index decreased from 3.35 ± 0.57 bits in 2004 to 1.98 ± 0.73 bits in 2014. The average density of dbh trees ≥ 10 cm decreased from 740.37 ± 269 , 86 stems / ha in 2004 to 184 ± 100 stems / ha in 2014. The results of the 5% sample matched t-test reveal a non-significant difference between the Shannon Diversity Index of 2004 and of 2014. On the other hand, the results of the sample t-test matched at the 5% threshold, reveal a significant difference between the average density value of 2004 and 2014 for all vegetation types except shrub savannas, fields and fallows. Most of the plant species found before the management plan are still present despite the decreased in individuals’ density.
Keywords: impact; inventories; management plan; vegetation; Wari-Maro.